Experience with SARS-CoV-2 in an orthopaedic hospital. Issue 1 (March 2023) - Oliveira, Priscila R.; Carvalho, Vladimir C.; Anjos, Angelica M.; Melo, Vanessa F.; Leite, Cesar; Silva, Adriana C.; Maluf, Natalya Z.; Silva, Jorge S.; Lima, Ana Lucia L.
Summary: Background: Concerns about nosocomial transmission of SARS-CoV-2 have been described since the COVID-19 pandemic was first reported and cases of hospital-acquired (HA) COVID-19 and COVID-19 outbreaks have been reported even in clinical areas not intended for the specific care of COVID-19 and declared as "non-COVID" areas. Methods: Retrospective analysis of measures to prevent of hospital acquisition of COVID-19 in patients admitted to a tertiary referral specialist orthopaedic hospital in Brazil in which emergency care was maintained during the pandemic. Results: The proportion of HA-COVID-19 (0.07%) was lower than the value reported for general healthcare in Brazil (0.72%, P <0.001). The integration of several clinical teams to maintain a constant surveillance system, as well as the immediate isolation of patients with any compatible symptoms of COVID-19 and the restriction from work and the testing of symptomatic healthcare workers, were an important part of the strategies adopted. Conclusion: We suggest that the described strategies for preventing the nosocomial spread of SARS-CoV-2 contributed to the observed proportion of HA-COVID-19 to be significantly lower than the reported national value. Future studies that investigate these and other preventative measures are important so that hospitals are prepared for further periods of a high incidence of COVID-19, as well as for other epidemics associated with respiratory transmission.